Comparative Metagenomics of Viral Assemblages Inhabiting Four Phyla of Marine Invertebrates - Gudenkauf, Brent M.; Hewson, Ian (Frontiers in Marine Science, 2016)
Viruses are the most abundant biological entities on Earth, killing 10-20% of oceanic biomass each day. However, despite their ecological importance, viruses inhabiting many echinoderms, cnidarians, urochordates, and marine arthropods have not been investigated with significant breadth. We conducted a broad survey of the viral assemblages inhabiting these hosts through viral metagenomics and phylogenetic analysis. Results indicate that different invertebrate groups harbor distinct viral assemblages. Interestingly, however, no significant difference is observed between the viral assemblages of echinoderms and arthropods. These similarities and differences may be due to cellular, immunological, geographical, and ecological differences amongst host phyla, although mechanistic determination is beyond the purview of this work. Additionally, we present evidence of the detection of several viral families that have not yet been observed in these hosts. Finally, we confirm the result of previous investigation that method of library construction significantly biases metagenomic results by altering the representation of of ssDNA and dsDNA viral genomes.